Israel's securitization dilemma : BDS and the battle for the legitimacy of the Jewish state - Olesker, Ronnie ([Place of publication not identified] : Routledge, 2021)
"This book examines how the Zionist movement, and later the state of Israel, have dealt with various longstanding efforts to delegitimize Israel's standing in the international community, including by the Arab League Boycott, the United Nations, and the Boycott, Divest and Sanctions (BDS) movement. Through historical and archival research, as well as discourse analysis and interviews with Israeli policy makers, this book argues that Israel has constructed perceived and real challenges to its legitimacy as ontological threats that undermine its national security, and has securitized its Jewish identity in response to these threats. As a result, the state has adopted extraordinary measures, often marked by illiberalism. Rather than enhance Israel's international legitimacy, these measures have undermined it further, especially among liberal audiences in the West, whose support is critical for Israel's continued international legitimacy. Therefore, Israel is locked in a securitization dilemma - where actions taken to enhance its security through increased legitimacy result in further delegitimization. Highlighting the ways this securitization dilemma is at the heart of Israeli policymaking today - particularly in the context of the recent BDS movement - this book brings into focus key problems that Israel faces as it attempts to combat delegitimization movements against its self-constructed identity as a Jewish state. This book will be of great interest to students, scholars and policymakers engaged with critical security studies and delegitimization, Israeli studies and Jewish identity, and policymaking in the Middle East"--
Israel's Securitization Dilemma -- Ontological Insecurity and the Securitization of the Jewish Identity of the State -- The Arab Boycott and Early Israeli Debates on the Threats of Delegitimization -- BDS and the Battle for Israel's Legitimacy -- The Losing Battle -- Resolving the Securitization Dilemma
OCLC-licensed vendor bibliographic record.
Keywords: POLITICAL SCIENCE / General; National security -- Israel; Legitimacy of governments -- Israel; Boycott, divestment, and sanctions movement; Arab-Israeli conflict; Zionism; Jews -- Israel; Israel -- Politics and government